The art of vanishing : a novel - Pager, Morgan (Ballantine Books, 2025)
"Jean's life is the same day in and day out. Frozen in time by his painter father, the legendary Henri Matisse, Jean observes the ebb and flow of museum guests as they take in the works of his father and other masters like Renoir, Picasso, and Modigliani. But his world takes a mesmerizing turn when Claire, a new museum employee, enters his life. Night after night, Claire moves through the gallery where Jean's painting hangs, mopping the floors, talking softly to herself to stem her loneliness, and gazing admiringly at the masterpieces above. The alluring man in the corner of the Matisse--is he watching her? Why does she feel a deepening pull to him, like he can see her truest self, her most profound secrets? Did he just move? In an extraordinary twist of fate, Claire discovers she can step through the frame of Jean's painting and into a bygone era, a lush, verdant snapshot of family life in France in the throes of the First World War. She and Jean begin a seemingly impossible affair, falling in love against the backdrop of the gallery's other paintings come to life--glittering parties, exhilarating horse races, and windswept beach bluffs--which they can move through together and where Claire is seemingly the only outside visitor, alone in possession of this gift. But as their happiness is threatened by challenges both inside and outside the museum, Claire and Jean find themselves in a fight to preserve the love they've hardly dared to dream of. Will their extraordinary connection defy the confines of reality, or will the forces conspiring against them shatter their carefully curated happiness?" --